A review of ship surveys practices and of marine casualties partly due to aging effects - RIZZO, CESARE MARIO; LO NIGRO A. (Volume 2: Structures, Safety and Reliability, 2008)
The first part of this paper overviews the present international regulatory regime and the future expected developments of ship surveys, from the viewpoint of methods and criteria, identifying different degradation phenomena mainly related to aging of structures and hull equipment. The current onboard practice is recalled, both of mandatory surveys (including class surveys and particularly the new requirements introduced by the IACS Common Structural Rules) and of non mandatory industry-driven inspections. Then, reviews of few databases of marine casualties, available to authors, are presented aiming at assessing the role of aging effects in the marine accidents. Even if it should be admitted that available statistical samples are not always complete and accurate, the intent is to identify trends in the pattern of structural failures and to develop recommendations for improving the inspection regimes and procedures for condition assessment analyses by which to reduce the number and severity of such occurrences.